Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)\((\dfrac{5}{7}x^2y)^3:(\dfrac{1}{7}xy)^3\)
=\((\dfrac{5}{7}x^2y:\dfrac{1}{7}:x:y)^3\)
=(\(\dfrac{5}{7}.7.x^2:x.y:y)^3\)
=(5x)\(^3\)
=5\(^3\).x\(^3\)
=125.x\(^3\)
a: \(=6x^4-9x^3+3x^2-4x^3+6x^2-2x+10x^2-15x+5\)
\(=6x^4-13x^3+19x^2-17x+5\)
b: \(=6x^4-\dfrac{9}{4}x^3-\dfrac{9}{2}x^2-\dfrac{8}{3}x^3+x^2+2x-\dfrac{20}{3}x^2+\dfrac{5}{2}x+5\)
\(=6x^4-\dfrac{59}{12}x^3-\dfrac{67}{6}x^2+\dfrac{9}{2}x+5\)
c: \(=3x^4-\dfrac{9}{8}x^3-\dfrac{3}{4}x^2+8x^3-3x^2-6x-\dfrac{4}{3}x^2+\dfrac{1}{2}x+1\)
\(=3x^4-\dfrac{55}{8}x^3-\dfrac{25}{12}x^2-\dfrac{11}{2}x+1\)
a: \(=\dfrac{4x^2+4x+1-\left(4x^2-4x+1\right)}{\left(2x-1\right)\left(2x+1\right)}\cdot\dfrac{5\left(2x-1\right)}{4x}\)
\(=\dfrac{8x}{2x+1}\cdot\dfrac{5}{4x}=\dfrac{10}{2x+1}\)
c: \(=\dfrac{1}{x-1}-\dfrac{x\left(x-1\right)\left(x+1\right)}{x^2+1}\cdot\left(\dfrac{x+1-x+1}{\left(x-1\right)^2\cdot\left(x+1\right)}\right)\)
\(=\dfrac{1}{x-1}-\dfrac{x}{x^2+1}\cdot\dfrac{2}{\left(x-1\right)}=\dfrac{x^2+1-2x}{\left(x-1\right)\left(x^2+1\right)}=\dfrac{x-1}{x^2+1}\)
a: \(=x^3+4x^2+16x+64\)
b: \(=8x^3-60x^2+150x-125\)
c: \(=\dfrac{1}{8}-\dfrac{3}{4}x^2+\dfrac{3}{2}x-x^3\)
d: \(=-\left(27x^3+54x^2y+36xy^2+8y^3\right)\)
f: \(=x^3+x^2y^2+\dfrac{1}{3}xy^2+\dfrac{1}{27}y^6\)
1: \(=\left(\dfrac{1}{2}:\dfrac{-2}{3}\right)\cdot\left(a^m:a^2\right)\cdot\left(b^n:b\right)\cdot\left(c^2:c\right)\)
\(=\dfrac{-3}{4}a^{m-2}b^{n-1}c\)
2: \(=\dfrac{2}{7}\left(x-2y\right)^{2m+1}\cdot\dfrac{-14}{5\left(2y-x\right)^{2m-1}}\)
\(=\dfrac{-4}{5}\cdot\dfrac{-\left(2y-x\right)^{2m+1}}{\left(2y-x\right)^{2m-1}}=\dfrac{4}{5}\cdot\left(2y-x\right)^2\)